Resistance From Within: Power and Defiance in Montesquieu’s - Jennifer Epley Sanders (SAGE Open, 2020)
Montesquieu reflects on the intricacies of government, social customs, and identity in his epistolary novel titled Persian Letters (1721). For many of these topics, Montesquieu addresses the themes of power and agency, mainly in the context of despotism as symbolized by a seraglio in the book. This article uses the explanatory research method through a case analysis of “power” in the Persian Letters to facilitate a nuanced, gendered understanding of “power” as a concept. The case analysis incorporates and applies feminist perspectives on power, as well as a theoretical framework and empirical observations from Scott’s Weapons of the Weak (1985), to define and operationalize “despotic power” and “defiant power.”